Analisis Faktor-Faktor yang Memengaruhi Economic Complexity di Negara-Negara Anggota BRICS+ - Nazwa Anggita; Sri Indah Nikensari; Siti Fatimah Zahra (Indo Publishing, 2026)
This study aims to analyze the factors influencing economic complexity in BRICS+ member countries. Economic complexity reflects a country's ability to produce diverse, high-value-added, knowledge-based, and technology-based products. This research is motivated by the varying capacities of BRICS+ countries in managing investment, human capital quality, and innovation to enhance more modern and competitive economic structures. The study employs a quantitative approach using panel data regression with the Fixed Effect Model (FEM) as the best-fit model. The dependent variable is economic complexity, while the independent variables consist of FDI, education level, and innovation. The results indicate that FDI has a positive but insignificant effect on economic complexity, suggesting that foreign investment remains concentrated in primary sectors and low-technology industries. Education level and innovation have a positive and significant effect on economic complexity, with innovation being the most dominant factor. Simultaneously, all three variables influence economic complexity. This study concludes that enhancing economic complexity in BRICS+ countries is more strongly driven by education and innovation than by FDI.